A study on the factors contributing to the performance of retails SMES in Melaka Tengah / Mohamad Sharul Nizam and Mohd Khairi Naziefatul Hana Zakaria - Mohd Khairi, Mohamad Sharul Nizam; Zakaria, Naziefatul Hana (Faculty of Administrative Science and Policy Studies, 2013)
The study seeks to determine the factors contributing to the successfulness of retail SMEs in Melaka Tengah. A sample of 108 of 146 SMEs Entrepreneurs who are bumiputera and registered with Pusat Khidmat PKS Melaka at Melaka Tengah had been selected for this study. The findings showed that the independent variables or factors that support our hypothesis are government’s efforts in implementing NKEA, application of information technology, human capital development, and availability of financial resources. Simple random sampling will be used to distribute questionnaire to selected respondents. To conclude based on the findings, all those four independent variables have significant relationship with successfulness of SMEs.